Combinatorial Effects of Aromatic 1,3-Disubstituted Ureas and Fluoride on In vitro Inhibition of Streptococcus mutans Biofilm Formation - Kaur, Gurmeet; Balamurugan, P.; Uma Maheswari, C.; Anitha, A.; Princy, S. Adline (Frontiers in Microbiology, 2016)
Dental caries occurs as a result of disequilibrium between acid producing pathogenic bacteria and alkali generating commensal bacteria within a dental biofilm (dental plaque). S. mutans has been reported as a primary cariogenic pathogen associated with dental caries. Emergence of multidrug resistant as well as fluoride resistant strains of Streptococcus mutans due to over usage of various antibiotics is a rising problem and prompted the researchers worldwide to search for alternative therapies. In this perspective, the present study was aimed to screen selective inhibitors against ComA, a bacteriocin associated ABC transporter, involved in the quorum sensing of S. mutans. In light of our previous in silico findings, 1,3- disubstituted urea derivatives which had better affinity to ComA were chemically synthesized in the present study for in vitro evaluation of S. mutans biofilm inhibition. The results revealed that 1,3- disubstituted urea derivatives showed good biofilm inhibition. In addition, the synthesized compounds exhibited potent synergy with a very low concentration of fluoride (31.25 ppm to 62.5 ppm) in inhibiting the biofilm formation of S. mutans without affecting the bacterial growth. Further, the results were confirmed by confocal laser scanning microscopy. On the whole, from our experimental results we conclude that the combinatorial application of fluoride and disubstituted ureas has a potential synergistic effect which has a promising approach in combating multidrug resistant and fluoride resistant S. mutans in dental caries management.